Saussure semiotic of animals in Zootopia (2016) - Krisna Novendra Haris; Mia Fitria Agustina; Ririn Kurnia Trisnawati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2021)
This study aims to find out the meaning of the animal characters in the Zootopia movie. Zootopia is an animated movie that uses animals as characters; thus, it is challenging to analyze those animals since they brought different signs from common ones. Therefore, this research focuses on three animal characters e.g., mouse, rabbit, and fox which are considered as important signs in Zootopia that thus need to be interpreted. In interpreting the signs, this study employs Saussure's semiotic theory which relates to a sign that contains a signifier and its use or interpretation as signified. This research used qualitative methods. It is found that the stereotypes of the three animal characters in the movie are different from the common acceptance. The movie tries to break stereotypes about mouse, rabbit and fox. Finally, it is hoped that this study may create more awareness to see anything not based on its prevailing labels.